Inducing isotropic growth in multidimensional cesium lead halide perovskite nanocrystals - Bhaumik, Saikat (2020)
A new two‐step synthetic protocol to yield monodisperse spherical zero‐dimensional (0D) Cs4PbX6 nanocrystals (NCs) and three‐dimensional (3D) CsPbX3 NCs is described. The first step of the reaction involves the colloidal synthesis of spherical PbX2 seed NCs, which are subsequently converted to Cs4PbX6 and CsPbX3 NCs through hot injection of a Cs precursor at the desired reaction temperatures. By employing less reactive Pb and halide precursors, the reaction time was extended from several seconds to about five minutes, thereby allowing greater control during the crystallization and growth stages. The adjustment of halide ratios allows color tuning over a wide spectral range (411–669 nm) for CsPbX3 NCs, with high photoluminescence quantum yields (6–65 %) and narrow emission line widths (ca. 13–30 nm). We envisage our spherical NCs to become a starting point for shell growth (e.g., ZnS, CdS, PbS) by overcoming the difficulty of shell growth around thermodynamically unfavorable (i.e., high surface free energy) cuboid‐shaped NCs.